Spirometric reference values in healthy, non-Smoking, Iraqi population (Iraqi Journal of Medical Sciences, 2009)
Background: Pulmonary function test depends on a number of physiological factors as height, age, gender and race. Reference mathematical equations are used to determine a normal range of spirometric results which in turn are used clinically to determine whether the results measured in any individual fall within a range to be expected in a healthy person of the same gender, height and age.Objectives: To derive the prediction equation for healthy, non smoking Iraqi subjects.Methods: The study was conducted in Baghdad (IRAQ) on one hundred eighty two (182) healthy, nonsmoking subjects between 20 to 60 years of age were included in the study. The subjects included were 79 males and 103 females whose pulmonary volumes and capacities were measured by spirometry. Results: The prediction equation was derived first and then the reference values were then calculated for forced expiratory volume in 1st second (FEV1) and force vital capacity (FVC). The values for both parameters were found to be lower by about 5.58% and 6.14% in females and 4.78% and 12.65% in males, respectively, when compared to researchers done on Caucasians.Conclusion: Pulmonary function test reference values and prediction equations for both sexes between the ages of 20-60 years were derived for a sample of healthy, nonsmoking, Iraqi population. A considerable difference was found between prediction equations and reference values obtained in present study compared with other studies conducted in western countries.Keywords: FEV1, FVC, Spirometry, Iraqi subjects